Recurrent Syncope following Substance Abuse; a Case Report - Salehi, Forod; Hassanzadeh Taheri, Mohammad Mehdi; Riasi, Hamid Reza; Mehrpour, Omid (Archives of Academic Emergency Medicine, 2017)
Drug abuse is considered as the most common poisoning in the world. Stimulants agent especially amphetamines and methamphetamines are among important abused substances. Different types of neurologic, psychiatric, respiratory, gastrointestinal, and cardiogenic complications have been reported to be related to methamphetamine consumption. Some of these substances could cause dysrhythmias which is the most prevalent etiology of cardiogenic syncope. Ecstasy, as one of the most commonly abused drugs, is known as a cause of cardiac dysrhythmias. Here we report a young boy who was admitted into the emergency department following three syncope attacks. All cardiac and neurologic assessments were normal; and finally ecstasy abuse was detected as the main etiology of syncopes.